Treatment of multiple adjacent gingival recessions in a single surgical approach with expanded subepithelial connective tissue graft - An innovative approach - Rameshwari Singhal; Pavitra Rastogi; Nandlal (Elsevier, 2012)
Background: Gingival recession on anterior teeth compromises facial esthetics and is associated with dentinal hypersensitivity. Multiple teeth recession requires multiple surgeries for adequate coverage. Methods: Six anterior mandibular teeth were treated with single Subepithelial Connective Tissue Graft (SCTG) expanded with the use of alternate vertical incisions. A brief review of SCTG is included. Results: 90 days evaluation revealed adequate recession coverage. Patient was satisfied with the esthetic results. Conclusion: The present technique may be an innovative approach for single surgical harvesting and placement of SCTG over long expanse multiple adjacent gingival recessions. This technique prevents multiple surgical traumas to the patient and enhances esthetics.